Role of computed tomography in transcatheter aortic valve implantation and valve-in-valve implantation: complete review of preprocedural and postprocedural imaging. Issue 3 (March 2020) - Chiocchi, Marcello; Ricci, Francesca; Pasqualetto, Monia; D'Errico, Francesca; Benelli, Leonardo; Pugliese, Luca; Cavallo, Armando Ugo; Forcina, Marco; Presicce, Matteo; De Stasio, Vincenzo; Di Donna, Carlo; Di Tosto, Federica; et al.
Abstract : N/A: Since 2002, transcatheter aortic valve implantation (TAVI) has revolutionized the treatment and prognosis of patients with aortic stenosis. A preprocedural assessment of the patient is vital for achieving optimal outcomes from the procedure. Retrospective ECG-gated cardiac computed tomography (CT) today it is the gold-standard imaging technique that provides three-dimensional images of the heart, thus allowing a rapid and complete evaluation of the morphology of the valve, ascending aorta, coronary arteries, peripheral access vessels, and prognostic factors, and also provides preprocedural coplanar fluoroscopic angle prediction to obtain complete assessment of the patient. The most relevant dimension in preprocedural planning of TAVI is the aortic annulus, which can determine the choice of prosthesis size. CT is also essential to identify patients with increased anatomical risk for coronary artery occlusion in Valve in Valve (ViV) procedures. Moreover, CT is very useful in the evaluation of late complications, such as leakage, thrombosis and displacements. At present, CT is the cornerstone imaging modality for the extensive and thorough work-up required for planning and performing each TAVI procedure, to achieve optimal outcomes. Both the CT procedure and analysis should be performed by trained and experienced personnel, with a radiological background and a deep understanding of the TAVI procedure, in close collaboration with the implantation team. An accurate pre-TAVI CT and post-processing for the evaluation of all the points recommended in this review allow a complete planning for the choice of the valve dimensions and type (balloon or self-expandable) and of the best percutaneous access.